Chinese Cabbage Plant (Brassica Rapa) Test Of The K01 Variety On The Total Concentration Of AB Fertilizer - Syahrin, Alfi; Alridiwirsah; Zaidat, Farah (Agricultural Science, 2025)
This study aims to evaluate the response of K01 variety of Chinese cabbage (Brassica rapa) to different concentrations of AB fertilizer in a hydroponic system. The experiment was conducted for six weeks at the Horticulture Research Center, MARDI Serdang, Malaysia, using a Completely Randomized Design (CRD) with five AB fertilizer concentration treatments (T1 to T5), five replications, and six samples per replication. The tested AB fertilizer concentrations ranged from 0.8 to 2.0 EC. Parameters observed included leaf number, plant height, chlorophyll content, and leaf area index (LAI). The results showed that treatments with higher AB fertilizer concentrations (T2 and T3) produced the best results in leaf number, reaching 33.4 leaves by the sixth week. In contrast, treatments with lower AB fertilizer concentrations (T1 and T4) resulted in lower leaf numbers. This study concluded that optimal AB fertilizer concentrations can enhance leaf number and growth of K01 variety Chinese cabbage in a hydroponic system. Therefore, proper fertilizer concentration management is crucial in hydroponic cultivation of Chinese cabbage to achieve maximum growth.